PENGEMBANGAN “SIMEZA” (APLIKASI MENGENAL ZAKAT) DALAM MATA PELAJARAN PAI UNTUK MEMBANTU PEMAHAMAN SISWA KELAS 6 SD - Azkia, Ravida; Puspitasari, Nurcahyani; Nur Aeni, Ani (EduStream: Jurnal Pendidikan Dasar, 2024)
The world of education is no longer unfamiliar with the terms learning media, teaching tools, and so on. In this era of modernization, everything is required to be completely digital, even remote areas must follow current developments so as not to be left behind. So that the students' learning process must be digitally based. This is what underlies the presence of SIMEZA (Application for Getting to Know Zakat) as a solution to help teachers present learning material about zakat in a more interactive and interesting way. SIMEZA was designed in response to the need for a more dynamic and interesting learning approach for students, especially in the midst of the transformation towards digital-based learning. By using SIMEZA, teachers can easily integrate zakat concepts into their learning, creating a more enjoyable and interesting learning experience for students. Through the D&D (Design and Development) research method and data collection techniques through interviews and filling out questionnaires by PAI subject teachers in elementary schools. Implemented at SDN Sukasirna I Sumedang, SIMEZA was successfully proven to be an effective and innovative learning tool. With trial results showing significant benefits in the process of delivering zakat material in class VI, SIMEZA strengthens its relevance as an educational solution that meets the demands of this digital era.